1985
DOI: 10.1093/jn/115.2.252
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc Deficiency on Methionine Metabolism, Methylation Reactions and Protein Synthesis in Isolated Perfused Rat Liver

Abstract: A perfusion technique was utilized to assess the rate of absorption and metabolism of L-methionine by livers isolated from rats fed a diet deficient in zinc. The endogenous concentration of S-adenosyl-L-methionine in the livers from the zinc-deficient rats was near normal, while the concentration in pair-fed controls was approximately 50% of that found in normal livers (ad libitum fed). The rate of uptake of methionine by the livers isolated from zinc-deficient rats was significantly less than in the pair-fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 47 publications
7
48
0
1
Order By: Relevance
“…There are very few studies that have investigated the relationship between Zn and hypomethylation. However, in one of the previous studies, Zn deficiency was found to reduce the utilisation of methyl groups from SAM in rat liver, resulting in genomic DNA hypomethylation and histone hypomethylation (Duerre and Wallwork 1986;Wallwork and Duerre 1985). This could lead to an increase in MN formation in Zn-depleted cells, as observed in the present study due to whole chromosome loss and malsegregation caused by altered structure of pericentromeric DNA and failure of kinetechore assembly at centromeres ).…”
Section: Discussionsupporting
confidence: 44%
“…There are very few studies that have investigated the relationship between Zn and hypomethylation. However, in one of the previous studies, Zn deficiency was found to reduce the utilisation of methyl groups from SAM in rat liver, resulting in genomic DNA hypomethylation and histone hypomethylation (Duerre and Wallwork 1986;Wallwork and Duerre 1985). This could lead to an increase in MN formation in Zn-depleted cells, as observed in the present study due to whole chromosome loss and malsegregation caused by altered structure of pericentromeric DNA and failure of kinetechore assembly at centromeres ).…”
Section: Discussionsupporting
confidence: 44%
“…Rats fed Zn-deficient diets have markedly decreased liver DNA methylation status (47) . The methionine cycle, key in the production of the universal methyl donor S-adenosylmethionine, is sensitive to a number of micronutrient deficiencies including Zn (48) .…”
Section: Epigenetic Regulation Of Gene Expressionmentioning
confidence: 99%
“…The principal metabolic role of micronutrients such as folate is to generate the one-carbon cycle intermediate and universal methyl donor SAM. Not surprisingly, more direct disruption of nutrient-dependent SAM-derived methyl group generation also results in hypomethylation of genomic DNA (40). However, changes in "global" genomic methylation do not necessarily translate to altered promoter methylation states at specific loci (41,42), demonstrating that the mechanisms underlying DNA methylation are tightly directed and regulated rather than passive.…”
Section: Discussionmentioning
confidence: 99%